2016
DOI: 10.1016/j.aop.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic model of quantum butterfly effect: Out-of-time-order correlators and traveling combustion waves

Abstract: We extend the Keldysh technique to enable the computation of out-of-time order correlators such as O(t)Õ(0)O(t)Õ(0) . We show that the behavior of these correlators is described by equations that display initially an exponential instability which is followed by a linear propagation of the decoherence between two initially identically copies of the quantum many body systems with interactions. At large times the decoherence propagation (quantum butterfly effect) is described by a diffusion equation with non-line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
305
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(329 citation statements)
references
References 43 publications
11
305
5
Order By: Relevance
“…3 While this connection between transport properties and chaos was first proposed in the holographic models, it has been also observed in condensed matter systems [14,[16][17][18]. 4 In [23], it was also shown that the diffusion constant may vanish across the phase transition, implying a dynamical transition to an many-body localization phase.…”
Section: Jhep06(2017)030mentioning
confidence: 99%
“…3 While this connection between transport properties and chaos was first proposed in the holographic models, it has been also observed in condensed matter systems [14,[16][17][18]. 4 In [23], it was also shown that the diffusion constant may vanish across the phase transition, implying a dynamical transition to an many-body localization phase.…”
Section: Jhep06(2017)030mentioning
confidence: 99%
“…[17]. In this work a relation between the entanglement entropy growth and the spreading of the OTOC was also conjectured [17] (c.f. Ref.…”
mentioning
confidence: 95%
“…(1.8) which diagnoses the quantum butterfly effect [22][23][24][25] and has been applied to various models recently [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. There are also experimental measurements of OTOC in different systems [43,44].…”
Section: Jhep07(2017)150mentioning
confidence: 99%